SEMANTICS OF NOUN PHRASEOLOGISMS WITH AN ADJECTIVAL ELEMENT IN THE RUSSIAN LANGUAGE - Sataeva M. (Vestnik Issyk-Kulʹskogo universiteta)
This article is dedicated to the study of the semantics of noun phraseologisms with an adjectival component in the Russian language. Noun phraseologisms containing adjectives play a significant role in enriching the flow of speech, contributing to a more precise and expressive designation of objects, phenomena, and their qualities. Phraseologisms occupy an important place in the language system, representing stable units of speech that possess a holistic meaning distinct from the meanings of their individual components. An important aspect of phraseological expressions is their ability to convey complex ideas, emotions, and evaluations through figurative constructions. Special attention is given to noun phraseologisms—expressions where the central part is a noun, but the adjectival component adds additional shades of meaning, making the analysis of these units particularly interesting. The aim of this article is to investigate the semantic structure of noun phraseologisms with an adjectival component. We will examine how the interaction between the noun and the adjective determines the overall meaning of the phraseologism, as well as classify the main types of such expressions based on their semantic content.